ABOUT THE HISTORY OF THE NEWSPAPER OF THE TURKISTAN REGION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
One of the publications that has taken an important place in the history of the Uzbek press is the "Turkeston Viloyat Gazeta". This newspaper was founded at the end of the 19th century, namely in 1870, and is considered one of the oldest mass media that initiated the first stage in the development of the Uzbek press. The emergence of the "Turkeston Viloyat Gazeta" was not only the emergence of a new source of information, but also served as an important tool in covering the political, social and cultural environment of that time.